MK2-mediated AKT/MYC signaling activation promotes epithelial-mesenchymal transition in lung adenocarcinoma - Qi, Rong; Fang, Chen; Liu, Penghui; Gu, Weiguo; Shi, Chao; Zhang, Guohua; Qiu, Feng (Frontiers in Genetics, 2025)
PurposeThe protein kinase Mitogen-Activated Protein Kinase-Activated Protein Kinase 2 (MK2) is linked to higher risks of metastasis and mortality in some cancers. Nonetheless, its precise function in lung adenocarcinoma (LUAD) remains unclear. This study aims to explore MK2’s function in LUAD cells and identify the underlying molecular mechanisms.MethodsMK2 expression in LUAD patients was confirmed through Timer2.0 database and tissue microarrays. Immunohistochemical staining for MK2 was performed on LUAD samples to investigate its association with metastasis and invasion. The activity of MK2 was inhibited in LUAD cell lines A549 and H358 using a specific MK2 inhibitor. Subsequently, cell viability, migration, and invasion were assessed. Gene expression changes were confirmed through Western blotting. Additionally, an AKT activator was used to validate the role of the MK2-regulated AKT/MYC signaling pathway.ResultsMK2 expression is significantly higher in LUAD tissues compared to adjacent normal tissues. Reducing MK2 activity not only curtails cell proliferation, migration, and EMT-related invasion in vitro but also disrupts the AKT/MYC signaling axis. Activation of the AKT/MYC pathway can counteract the inhibitory effects of MK2 suppression.ConclusionOur findings suggest that MK2 promotes migration and invasion in LUAD through the AKT/MYC signaling pathways, positioning MK2 as a potential therapeutic target in LUAD treatment.